Collateral, Netting and Systemic Risk in the OTC Derivatives Market - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2010)
To mitigate systemic risk, some regulators have advocated the greater use of centralized counterparties (CCPs) to clear Over-The-Counter (OTC) derivatives trades. Regulators should be cognizant that large banks active in the OTC derivatives market do not hold collateral against all the positions in their trading book and the paper proves an estimate of this under-collateralization. Whatever collateral is held by banks is allowed to be rehypothecated (or re-used) to others. Since CCPs would require all positions to have collateral against them, off-loading a significant portion of OTC derivatives transactions to central counterparties (CCPs) would require large increases in posted collateral, possibly requiring large banks to raise more capital. These costs suggest that most large banks will be reluctant to offload their positions to CCPs, and the paper proposes an appropriate capital levy on remaining positions to encourage the transition.